Prevalence and Associated Factors with Mixed Coinfections among under 5-Year-Old Children with Severe Viral Pneumonia in Vietnam - Pham, Hien T.; Nguyen, Tran N. T.; Tran, Quynh A.; Ngo, Tam T. (Journal of Child Science, 2020)
Community-acquired pneumonia (CAP) is well-recognized as a leading cause of disease burden in children. This study aimed to identify the prevalence of coinfection and associated factors in Vietnamese children ages 1 month to 5 years with viral pneumonia. We performed a cross-sectional study of children who were diagnosed with severe viral pneumonia. Demographic, clinical, and subclinical characteristics were compared between children with viral alone and bacterial coinfection. Multivariate logistic regression was used to determine which factors were associated with risk of coinfection. Of 202 children with severe viral pneumonia, the most common causative agent was respiratory syncytial virus (respiratory syncytial virus [RSV]: 36.1%), followed by influenza virus A (24.3%) and adenovirus (19.8%). Fifty-three children (26.2%) had bacterial superinfection and/or coinfection with other viruses. Haemophilus influenza was the most common bacterium (9.4%), followed by Klebsiella pneumoniae and Pseudomonas aeruginosa (with 4.0%). In infants (toddlers), ages 12 to 24 months with severe viral pneumonia, (odds ratio [OR] = 3.37, 95% confidence interval [CI]: 1.22–9.33), the higher concentrations of procalcitonin (PCT; OR = 1.16; 95% CI: 1.00–1.34), and neutrophils (OR = 1.13; 95% CI: 1.04–1.22) were associated with a higher risk of coinfection. This study underlined the pervasiveness of coinfections among young children with severe viral pneumonia. Provision of effective antiviral treatment, especially for RSV, as well as the advancement of sensitive and rapid diagnostic tools for screening pathogens of pneumonia, is critical to reducing the burden of this disease.
Keywords: bacterial; viral; severe pneumonia; coinfection